Colonialism in the margins : cultural encounters in New Sweden and Lapland - Fur, Gunlög (The Atlantic World, 2006)
The first book-length study of Swedish-Indian encounters in the New Sweden colony on the Delaware River focuses on land, trade and culture from the founding in 1638 until the 1680s, and compares these relations with Swedish interaction with Saami people.